Application of Geoinformation Technologies for Assessment of the Epizootiological and Epidemiological Situation on Anthrax in the Volgograd Region - A. G. Ryazanova; D. K. Gerasimenko; N. P. Buravtseva; V. M. Mezentsev; F. V. Logvin; T. M. Golovinskaya; O. V. Semenova; L. Yu. Aksenova; S. V. Perekhozheva; D. K. Chmerenko; A. N. Kulichenko (Проблемы особо опасных инфекций, 2022)
Objective of the study was to assess the epizootiological and epidemiological situation on anthrax in the Volgograd Region in the period of 1920–2019, to zone the territory according to the degree of disadvantage as regards anthrax using geographic information technologies. Materials and methods. The reporting data of the Rospotrebnadzor Administration, Veterinary Committee in the Volgograd Region, and literature sources were studied. ESRI-ArcGIS 10 software was used as a GIS-platform. Epizootic index was applied in the zoning according to the degree of disadvantage regarding anthrax in the territories of the region. Results and discussion. Currently, 529 stationary potentially hazardous as regards anthrax areas have been registered in 33 districts of the Volgograd Region, 53 anthrax burial sites are accounted for in 20 districts. During the period of 1970–2019, 226 cases of infection of farm animals and 37 cases of anthrax among humans were detected. Most of the stationary potentially hazardous as regards anthrax areas (347 sites, 66 %) were formed in 1930–1949. Maximum activity was observed in 1930–1959. The zoning of the territory of the Volgograd Region was carried out using ESRI-ArcGIS 10 software, as a result of which the municipal districts were divided into four groups according to the degree of disadvantage regarding anthrax. The potential of different soil and landscape zones in the persistence of the anthrax microbe was studied. It has been found that chernozem, chestnut, dark-chestnut soil types, which occupying more than 50 % of the total region area and predominate in the zones of moderately arid and dry steppes, alongside alluvial meadow soils of river valleys, floodplains of rivers are very favorable for the persistence of the anthrax pathogen. The territory of the Volgograd Region is endemic for this infection and epizootiological and epidemiological well-being in the region largely depends on the completeness and timelines of preventive measures. The use of geographic information technologies provides a comprehensive analysis of the infection activity manifestations with reliable improvement of the anti-anthrax surveillance system and control in making differentiated managerial decisions.